Impact of land uses in the hydrophysical functioning of the soil superficial horizon in Atlantic Forest domain - Serafim, Caio Rodrigues (2024)
The conversion of tropical forests to agricultural and livestock uses affects the soil\'s physical and water attributes, causing changes in the soil. However, there has been an increase in vegetation cover as a result of forest restoration actions to mitigate this damage, and the abandonment of agricultural land. These natural or restored forest ecosystems can provide ecosystem services, such as carbon sequestration, soil conservation, biodiversity maintenance, wood, fiber and food production, water regulation, among others. However, hydrological services, such as the infiltration of water into the soil promoted by these forests (new and remnant), have not yet been fully understood in ecological restoration, since there are still basic knowledge gaps in understanding the physical and hydrological processes of soils under forest restoration. In this context, our study aimed to investigate the effects of forest restoration and other land uses on soil physical and water properties in the Atlantic Forest domain in the state of São Paulo. The study sought to answer the following questions: (i) How do the attributes of the soil surface differ between pastures, natural forests, active restoration plantations and natural regeneration at different ages? (ii) Which of the physical attributes of the soil most influence the saturated hydraulic conductivity of the soil? To answer these questions, the following land uses were chosen: young active restorations (up to 16 years old), intermediate active restorations (over 17 years old), natural regenerations (between 30 and 77 years old), pastures and natural forests. The results showed that areas undergoing forest restoration via active restoration or natural regeneration were able to recover the attributes saturated hydraulic conductivity (Ks), penetration resistance (PR) and macro porosity (Mac) to levels similar to those of natural forests. In the active restorations, there was an improvement in the soil density (BD) and PR attributes in the older areas, showing an improvement over time after restoration. Natural regeneration was unable to recover BD to levels similar to natural forest, which can be attributed to the time it takes for these attributes to reach levels similar to natural forests. Total porosity was the attribute that most influenced Ks, regardless of land use, demonstrating the importance of porosity in soil water infiltration processes. We conclude that forest restoration actions via active restoration or natural regeneration can improve the soil\'s physical and hydrological attributes, but in natural regenerations, the recovery of soil attributes can be slower, taking more than 33 years to recover the soil\'s physical and water properties.